Pengaruh Pijit Bayi (pe’e) Tradisional Bima Terhadap Status Gizi Bayi Usia 5-12 Bulan di Kecamatan Bolo Kabupaten Bima - Kurniadi Kurniadi; Mardiatun Mardiatun (Bima Nursing Journal, 2019)
Massage will also stimulate the vagus nerve which will produce gastrin and insulin enzymes so that absorption of the digestive tract is better, the stomach is empty faster, and the baby will be hungry more often, so the baby will suckle more often, and the end result will be an increase in baby's weight. One of the most important indicators in assessing nutritional fulfillment in infants is taking into account body weight (Zulhaida, 2003). Weight is the most important anthropometric measure, used at every opportunity to examine the health of infants in all age groups (Soetjiningsih, 1998: 38). This research is a quasi-experimental study with pre and post test designs in the same group. The researcher will assess the nutritional status of infants aged 5-12 months before and after the traditional massage (pe'e). Sampling was carried out in Bolo Subdistrict, Bima District by using Purposive sampling, which was conducted in September to November 2018 with a total sample of 140 respondents. Data was collected using an observation sheet. The results of this study found that the weight of infants aged 5-12 months before peee was in the sub-normal category, the weight of infants aged 5-12 months experienced an increase after pe'e I and pe'e II, the results of data analysis found there was an influence weight gain before and after pee is done in infants aged 5-12 months